Differences in Managerial Quality of KPM Students (Muslim Student Community) and Non-Organizational Students - Ishak Risaldi; Zulfah Zulfah; Musyarif Musyarif (Jurnal Kajian Manajemen Dakwah, 2022)
This study discusses the influence of KPM (Muslim Student Community) cadre on managerial students at SMA Negeri 1 Parepare. The purpose of this study was to determine whether there is an effect of regeneration on the managerial quality of students by comparing students from KPM organizations with non-organizational students. This type of research is quantitative research. The number of samples is 80 with the distribution of 40 students from KPM organizations and students from non-organizations. The data collection instrument used a questionnaire. The data analysis technique used is the T-test. The results showed that: the regeneration of the KPM organization (Muslim Student Community) had no effect on the managerial quality of students. It can be seen from the overall managerial average of students is 69.25 and 66.40 with the same category, namely good. T-count and T-table with the condition that if T-count is greater than T-table, then Ha is accepted and H0 is rejected. If T-count is less than T-table, then Ha is rejected and H0 is accepted. So based on the results of calculations obtained the results of T-count 1.080 1.990 with a significant level of 5% so that it can be stated that H0 is accepted and Ha is rejected. From the results above, it can be concluded that there is no difference in the managerial quality of KPM students and non-organizational students